A LEADERSHIP AND COMPENSATION FACTORS IN MEASURING EMPLOYEE LOYALTY - Imamul Khaira; Nur Ainun; Refli Renaldi (Sean Institute, 2023)
Companies can achieve goals in the company required employees who have high loyalty to the company then they will have a willingness to work hard and a sense of security in a company. This study aims to see how the influence of organizational culture, leadership, compensation, and work environment on employee loyalty at PT Mitra Naga Sejati Jaya Langkat. This research uses quantitative methods with an associative approach. The population in this study was seventy-nine using saturated sampling technique where all members of the population were sampled as many as seventy-nine people. Data analysis methods used validity test, reliability test, classical assumption test, hypothesis testing, multiple linear regression, coefficient of determination.